Analisis Kesesuaian Akuntansi Transaksi Gadai Emas Syariah Dengan PSAK dan Fatwa DSN MUI (Studi Kasus Praktik Gadai Emas di Pegadaian Syariah Surabaya) - Rahman, Lina Aulia; Suprayogi, Noven (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
One easy and practical financing is a pawn. Pawning gold is very attractive financing for fast processing and high estimates. Basic mortgage financing in Indonesia sharia is Fatwa 25 / DSN-MUI / III / 2002 on Rahn and 26 / DSN-MUI / III / 2002 on the Gold Rahn, PSAK 59 (qardh), PSAK 107 (Ijarah), and PAPSI in 2013.This study aims to determine the accounting treatment products on the gold pawn Sharia Islamic Pawnshop Surabaya with gold pawn practice case studies on Islamic Pawnshop Blauran Surabaya Branch. This research is qualitative. The data collection methods used were interviews and take the financial statements on the official website Pawnshop. The results showed that the accounting treatment in the aspect of recognition and measurement in accordance with PSAK 107, PSAK 59, and PAPSI 2013. But, the presentation of the financial statements is not accordance with PSAK 100 and 101.